2014
DOI: 10.4314/tjpr.v13i5.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aspirin on Fractalkine in Rats with Pulmonary Embolism

Abstract: Purpose: To investigate the effect of aspirin on fractalkine (FKN) in rats with pulmonary embolism (PE and FKN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…CX3CL1 is important in the recruitment of inflammatory cells into the vascular wall in endothelial cell injury (12,13). Previous studies have reported that TNF-α stimulates the CX3CL1/CX3CR1 inflammatory signaling pathway, whereas our previous studies revealed that the expression levels of TNF-α, CX3CL1 and CX3CR1 were significantly increased in rats with pulmonary embolism (3,14). Certain studies have reported that the presence and the stimulation of the CX3CL1 receptor, CX3CR1, is correlated with the reduced release of IL-1β and TNF-α (15,16).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…CX3CL1 is important in the recruitment of inflammatory cells into the vascular wall in endothelial cell injury (12,13). Previous studies have reported that TNF-α stimulates the CX3CL1/CX3CR1 inflammatory signaling pathway, whereas our previous studies revealed that the expression levels of TNF-α, CX3CL1 and CX3CR1 were significantly increased in rats with pulmonary embolism (3,14). Certain studies have reported that the presence and the stimulation of the CX3CL1 receptor, CX3CR1, is correlated with the reduced release of IL-1β and TNF-α (15,16).…”
Section: Discussioncontrasting
confidence: 62%
“…Our previous studies demonstrated that a wide range of inflammatory responses, including the expression of tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-8, the irregular chemokine CX3C chemokine ligand 1 (CX3CL1) and its receptor CX3C chemokine receptor 1 (CX3CR1) were found in an APE rat model. In addition, the level of CX3CL1 was shown to positively correlate with the level of TNF-α (3,4). It was also found that lipopolysaccharide (LPS) can induce the expression of nuclear factor (NF)-κB and CX3CL1 in human bronchial epithelial cells (5), and it was found that aspirin improved the pathological changes in rats with APE via the CX3CL1/CX3CR1 signaling pathway (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, although inflammatory reactions contribute to the aggravation of thrombus formation, the relationship between the two factors needs to be further explored. Secondly, only five groups of rats have been established in this study, but aspirin as a control group was not established as in our previous study [1113]. This was done in order to decrease the unnecessary animal sacrifices.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboxane A2 (TXA2, Youersheng Science and Technology Co. Ltd., Wuhan, China), brain natriuretic peptide (BNP, Youersheng Science and Technology Co. Ltd., Wuhan, China), troponin I gene (TNNI3, Youersheng Science and Technology Co. Ltd., Wuhan, China), and D-Dimer (D2D, Youersheng Science and Technology Co. Ltd., Wuhan, China) levels in the rat serum were detected by a double-antibody sandwich enzyme-linked immunosorbent assay (ELISA). The specific experimental procedures used are based on our previously reported studies [1113]. Pulmonary pathology examined was as follows: after the examination of the gross pathology of the lung, lung tissue was fixed by 10% formalin for 24 h. The paraffin-embedded sections were prepared and then stained with a hematoxylin-eosin (H&E) reagent.…”
Section: Methodsmentioning
confidence: 99%